METHODOLOGY FOR TEACHING STUDENTS TO DESCRIBE A STILL LIFE COMPOSITION MADE UP OF HOUSEHOLD ITEMS IN PENCIL DRAWING SESSIONS - Ulfat Shuhratovich Ismatov (European Science Publishing, 2024)
In this article, the stages of drawing up a still life composition, consisting of household items, describing a still life composition in pencil, are shown in methodological consistency in fine art training.
Keywords: Still Life, light shade, fine art, pencil, household items.